(untitled) (Vietnam Journal of Community Medicine, 2022)
Background: Surgical treatment is an important method, applied to early stage uterine cancer patients. Objective: To evaluate the results of surgery for uterine cancer at Nghe An Obstetrics and Pediatrics Hospital. Methods: Retrospective and prospective cross-sectional description of 49 patients diagnosed with uterine cancer at Nghe An Obstetrics and Children’s Hospital from June 2020 to June 2022. Result: The average age of patients at the time of diagnosis was: 68 years old. Cervical cancer accounted for 79.6%, endometrial cancer accounted for 20.4%. The value of magnetic resonance in assessing and classifying uterine cancer stage: stage I is 83.3%, stage II is 85.7%, the total of both stages is 84.2%. Compared with the laparotomy method, laparoscopic surgery has many advantages: lower complication rate, shorter postoperative transit time, less blood loss, lower patient lower blood transfusion. Conclusion: Radical surgery at the beginning is indicated for FIGO stage I and II uterine cancer with good, safe treatment results and complications within acceptable limits.